2011
DOI: 10.1111/j.1365-2133.2011.10487.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B radiation and reactive oxygen species modulate interleukin-31 expression in T lymphocytes, monocytes and dendritic cells

Abstract: Our studies reveal that UVB and reactive oxygen species stimulate the expression of IL-31 in PBMCs and skin, especially in T cells, monocytes and monocyte-derived dendritic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…We further analyzed the impact of a co-culture of eosinophils with fibroblasts in relation to their IL-31 release (generation of fibroblasts see Supplementary Material and Methods S1 online) after 24 hours in culture. As already observed, fibroblasts secrete IL-31 (Cornelissen et al, 2011). However, the co-culture of eosinophils and fibroblasts did not further enhance IL-31 expression ( Figure 1g).…”
supporting
confidence: 76%
“…We further analyzed the impact of a co-culture of eosinophils with fibroblasts in relation to their IL-31 release (generation of fibroblasts see Supplementary Material and Methods S1 online) after 24 hours in culture. As already observed, fibroblasts secrete IL-31 (Cornelissen et al, 2011). However, the co-culture of eosinophils and fibroblasts did not further enhance IL-31 expression ( Figure 1g).…”
supporting
confidence: 76%
“…However, both human and murine IL-31 mRNA contain pentameric AUUUA sequences in their 3 0 UTR indicating that IL-31 like other inflammatory cytokines might be regulated on mRNA stability level. Indeed, Cornelissen et al found that inhibition of p38 MAPK activity reduced the stimulatory effect of H 2 O 2 on IL-31 expression which could be indicative of either a p38 MAPK-dependent transcription factor binding to the promoter or p38 MAPK being involved in regulating the mRNA stability [121].…”
Section: Transcription Biosynthesis and Secretion Of Il-31mentioning
confidence: 99%
“…Major sources this cytokine are activated CD4 + T lymphocytes, in particular activated T H 2 helper cells, mast cells, monocytes/macrophages and dendritic cells [39,[119][120][121] and its major target sites are the skin, lung, intestine and the nervous system (Fig. 4).…”
Section: Interleukin-31 (Il-31)mentioning
confidence: 99%
“…1 Additional cell types such as monocytes, macrophages, immature and mature dendritic cells and mast cells produce IL-31 following activation. [2][3][4][5] Increased IL-31 expression has been detected in inflamed tissues from patients with atopic dermatitis, bowel diseases, allergic asthma and rhinitis. [6][7][8][9][10][11][12] The activity of IL-31 is mediated through an heterodimeric receptor composed of a gp130-like receptor chain, IL-31 receptor A (IL-31RA) and the Oncostatin M Receptor (OSMR).…”
Section: Introductionmentioning
confidence: 99%